If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3(6) = 12 Multiply -3 * 6 4x + -18 = 12 Reorder the terms: -18 + 4x = 12 Solving -18 + 4x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 4x = 12 + 18 Combine like terms: -18 + 18 = 0 0 + 4x = 12 + 18 4x = 12 + 18 Combine like terms: 12 + 18 = 30 4x = 30 Divide each side by '4'. x = 7.5 Simplifying x = 7.5
| lnx=ln(x-7)+ln(5) | | 2(4r+8)-4(r+3)= | | (3t-4)(3t-4)-7(3t-4)+10=0 | | -3+5x+6=7x-4+5x | | 3+8n-1=-4n+2-5n | | 0=9x^4-25x^2 | | 4x+1=8x-5 | | 0.15x-3=0.3(x-7) | | -12=5-6n+11 | | 14+x=4 | | 50r^2-32= | | -3x=315 | | 3x+3(x-1)=9 | | 8x-5y=23 | | -y^2+x-4y-6=0 | | 7u=35 | | 2x+7=3+5x-8 | | (x+1)+x+(x-1)=90 | | .66x=4 | | .66n+6=18 | | 5x+8=4x | | y-0.19y= | | -1/2(16x+4/9)=3/7(-14x-28/9) | | 0=3x^2-5x | | .5b^2+3b-36=0 | | 6(y+6)=8y+36 | | -5x-3+4x=4 | | 17+5x=12x | | -5(m+2)-m-7=-6(m+4)+7 | | 7-7x=-2x-18 | | 8-3x=x+32 | | 2(14.6)+11=3(14.6)+6 |